The Features of Modern e-Marketing - SAFONOVA, Marina S.; IL'YASHCHENKO, Dmitry P.; KUCHEROV, Aleksey V.; LING, Viktoriya V.; SMIRNOVA, Zhanna V.; BUKHTIYAROVA, Irina N. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).30, 2018)
The selection is not resolved before the General problem. Some domestic scholars insist on the need to introduce special taxes for subjects of electronic business – the need to improve existing tax regimes, in particular, simplified, and introduction of tax privileges and preferences. Foreign experience of the taxation of electronic business is also contradictory – from strict state regulation through the introduction of special taxes to full tax exemption. While acknowledging the results of scientific research on this issue, we note that the General concept of taxation of e-business and is still not formed. So now the special relevance of the formation of the effective mechanism of taxation of e-business, and that led to the need for further research in this direction.